As to the concept of the subject of crimes against property - Олійник, П. В. (Problems of legality, 2015)
On the basis of the interpretation of generic subject of the property crimes under Section VI of the Special Part of the Criminal Code of Ukraine there have been distinguished the factors, which have significant impact on the definition of the essence of the target of such crimes. These are social, economic and legal factors. Also taking into account the nature of the impact of these factors on the target the author established the characteristics of generic subject of property crimes and gave its definition.